2012
DOI: 10.5173/ceju.2012.03.art4
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin as a prognostic factor for prostate cancer (PCa)

Abstract: IntroductionThe prostate cancer is difficult to predict, and treatment failure is associated with local infiltration, as well as distant metastases. Adhesion and migration abilities to of cancer cells play a major role in formation of metastasis. The participation of β-catenin in pathogene-sis of many types of cancer and benign processes has been an important discovery of recent years.Material and methodsThe studied material was obtained by transrectal, sextant core biopsy from 102 patients hospitalized in Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(32 reference statements)
3
9
0
Order By: Relevance
“…Upon Wnt ligand engagement, β-catenin is activated and disrupted, followed by its translocation from the cytoplasm into the nucleus, where it facilitates the transcription of genes involved in EMT, such as Twist, Snail, Slug, which repress the expression of E-cadherin, influencing cell junction and polarity (37). Previous studies have reported that overexpression and hyperactivation of β-catenin are observed in aggressive basallike breast cancer, and are positively correlated with poor patient clinical outcome (38)(39)(40). Therefore, β-catenin may be a novel therapeutic target with which to overcome breast cancer metastasis and improve the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upon Wnt ligand engagement, β-catenin is activated and disrupted, followed by its translocation from the cytoplasm into the nucleus, where it facilitates the transcription of genes involved in EMT, such as Twist, Snail, Slug, which repress the expression of E-cadherin, influencing cell junction and polarity (37). Previous studies have reported that overexpression and hyperactivation of β-catenin are observed in aggressive basallike breast cancer, and are positively correlated with poor patient clinical outcome (38)(39)(40). Therefore, β-catenin may be a novel therapeutic target with which to overcome breast cancer metastasis and improve the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of β-catenin and androgen receptor (AR) protein expression correlated with high Gleason grade, disease progression, and increasing serum prostate-specific antigen (PSA) levels in PCa patients [41]. The intensity of membrane associated β-catenin switched to cytoplasm was used to predict the higher risk of death in prostate cancer patients [42]. Our results revealed that CAPE treatment can significantly suppressed total and nuclear abundance of β-catenin (Figures 2, 3, 5), which may contribute to the inhibition of PCa metastasis caused by CAPE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Snail-induced EMT is partly due to the direct repression of E-cadherin transcription both during development and tumour progression (22). β-catenin serves a key role in regulating cell proliferation and differentiation (23,24). Epithelial integrity requires the stability of E-cadherin/β-catenin complexes (25).…”
Section: Introductionmentioning
confidence: 99%